1993
DOI: 10.1007/bf00321184
|View full text |Cite
|
Sign up to set email alerts
|

Herbivory of clonal populations: cattle browsing affects reproduction and population structure of Yucca elata

Abstract: The hypothesis that cattle browsing on inflorescences of the soaptree Yucca elata reduces reproductive success was investigated by comparing recruitment and population structure in six populations protected from grazing, six grazed during the flowering season and five grazed outside the flowering season. Cattle consumed 98% of inflorescences, which were found to be highly nutritious. Reduced recruitment in flower-grazed populations could not be attributed to reduced flower survival, as recruitment in non-flowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 7 publications
0
22
1
1
Order By: Relevance
“…Y. elata can recover from loss of more than 90% of the leaves by pack-rat (Neotoma spp.) herbivory and exhibits compensatory growth when the central cluster of leaves is removed by cattle (Kerley et al, 1992).…”
Section: Speciesmentioning
confidence: 99%
“…Y. elata can recover from loss of more than 90% of the leaves by pack-rat (Neotoma spp.) herbivory and exhibits compensatory growth when the central cluster of leaves is removed by cattle (Kerley et al, 1992).…”
Section: Speciesmentioning
confidence: 99%
“…Accordingly, disturbances in grazed sites were found to negatively influence the presence and establishment of herbivores (Kerley et al 1993), and intensive grazing was reported to disturb plant-insect interactions . Thus, in cases where formerly mown grasslands now have to be grazed to reduce labour, the number of cattle and the duration of grazing need to be limited.…”
Section: Leaf Damage By Herbivory and Fungal Pathogen Infectionmentioning
confidence: 99%
“…Such a population decline could have significant implications for a variety of animal species, including yucca moths (Tegeticula spp.) which are pollinators and seed parasites, carpenter bees (Xylocopa californica) which nest in inflorescence stalks, and a variety of birds (especially raptors) which use the dry stalks as one of the few natural tall perches in this landscape (Kerley et al, 1993).…”
Section: Discussionmentioning
confidence: 99%